Climate change and variability over Malaysia: gaps in science and research information - Fredolin T. Tangang,; Liew, Juneng; Ester Salimun,; Kwan, Meng Sei; Loh, Jui Le; Halimatun Muhamad, (Universiti Kebangsaan Malaysia, 2012)
This paper provides an overview of the current available scientific knowledge pertaining to climate change and climate variability over Malaysia. Malaysia is situated in the western part of the Maritime Continent of the Southeast Asian region. Hence, regional climate change and climate variability over this region are of central importance to the understanding of climate change in Malaysia. The latest regional climate downscaling study indicates that, depending on the emission scenario, the mean surface temperature over Malaysia would increase by 3-5oC by the end of the 21st century. The mean precipitation is projected to decrease (increase) during Northern Hemisphere winter (summer). However, future variabilities associated with regional phenomena such as the monsoon, El Nino-Southern Oscillation (ENSO), Indian Ocean Dipole (IOD) and Madden-Julian Oscillation (MJO) are largely unknown. Current knowledge on the intensity and frequency of future extreme events (drought and flood) is limited. This is also the case for regional sea level rise and long-term changes in regional seas, especially in the southern region of the South China Sea. We conclude that knowledge gap in the science of climate change over Malaysia and the surrounding region remains wide.